Climate-Resilient Traditional Architecture: A Case of Dharamshala, India - Kaundal, Geetika; Sharma, Puneet; Singh, Inderpal (Journal of Architectural/Planning Research and Studies (JARS), 2025)
The settlement typology of any region is determined by various climatic, cultural, and topographical dynamics. In mountainous regions, rapid and unregulated urban development often results in the emergence of an organic urban fabric that fails to meet the environmental needs of the area.It is important to thoroughly examine and analyse the traditional wisdom and techniques employed in designing buildings and settlements in mountainous regions. This study focuses on the exploration and understanding of traditional architecture in the hills of Dharamshala, India having composite climatic conditions. It aims at studying the role of traditional buildings, which are made of stone and mud having sloping roofs with bamboo and natural stone slates, in the context of resilience in disaster prone areas. The scope of this research is to establish the effectiveness of traditional building materials in maintaining the indoor comfort temperature in this region. A descriptive-interpretative approach was utilized to comprehensively understand and document the traditional designs and methods. Results show that half of the housing stock is still vernacular in form and traditional houses have 3℃-4℃ lower indoor temperatures in the hot season as compared to outdoor temperatures due to passive construction styles.